Legal responses to novel psychoactive substances implemented by ten European countries: An analysis from legal epidemiology - Jessica Neicun; Andres Roman-Urrestarazu; Katarzyna Czabanowska (Elsevier, 2022)
Introduction: Novel psychoactive substances (NPS) continue to pose challenges to law enforcement authorities, public health officers and policymakers as suppliers continuously adapt to control measures, thus remaining highly dynamic in introducing unpredictable and potentially toxic new substances into the drug market. Using a legal epidemiology approach, the aim of this study was to assess the effectiveness of NPS legal measures in preventing NPS use (legal prevention and control), as well as NPS-related intoxications and deaths (legal aetiology). Methods: We conducted a comparative analysis of legal instruments adopted at national level as a response to NPS by ten European countries between 2008 and 2019. The data collection process encompassed (i) a scoping review aimed at mapping out the current state of NPS-related legal measures, and (ii) the collection of nationally produced health data on three NPS-related health indicators (prevalence of use, acute intoxications and deaths). Results: Based on both the legal approaches and the regulatory model adopted by countries a five-elements typology was elaborated. Implemented measures - particularly individual listing - may be relatively effective in preventing NPS use, at least in the short-term. However, they are also very likely to affect the purity and potency of substances, which may have an indirect negative impact on users' health. In fact, an increase in NPS-related poisoning episodes and deaths has been observed in most of the countries having introduced control measures, regardless the regulatory model adopted. Conclusions: Policy responses to NPS implemented across Europe have not been markedly effective in deterring their use nor in preventing health harms. Therefore, there is a need for innovative initiatives to regulate drug markets that go beyond law enforcement. Considering scientific evidence on underlying factors leading to the use of psychoactive substances may better inform policy responses to address users' motivations while reducing their exposure to health risks.